A revision of the genus Trachelas L. Koch, 1872 (Araneae: Trachelidae) in the continental Afrotropical Region - Haddad, Charles R.; Lyle, Robin (Zootaxa, 2025)
The polyphyletic spider genus Trachelas L. Koch, 1872, with the type species T. minor O. Pickard-Cambridge, 1872 from Europe (also known in North Africa and Central Asia), has a worldwide distribution in the tropical, subtropical and temperate regions, although Trachelas sensu stricto is restricted to the Old World. Here the continental Afrotropical species are revised and a description of Trachelas sensu stricto is provided. Trachelas canariensis Wunderlich, 1987, T. chubbi Lessert, 1921, T. pusillus Lessert, 1923 and T. sylvae Caporiacco, 1949 are redescribed, and the female of T. pusillus described for the first time. Seven new species are described: T. falsus sp. nov. (♂ ♀, Côte d’Ivoire, Nigeria, South Africa and Tanzania), T. humus sp. nov. (♂ ♀, Namibia and South Africa), T. leggi sp. nov. (♂ ♀, South Africa), T. longinquus sp. nov. (♂, Central African Republic), T. russellsmithi sp. nov. (♀, Ethiopia), T. scutatus sp. nov. (♂ ♀, Ghana and Nigeria) and T. smithi sp. nov. (♀, Kenya). The female of Trachelas scopulifer Simon, 1896 is redescribed, its male is described for the first time, and its transfer to Thysanina Simon, 1910 proposed. The immature female type of T. punctatus Simon, 1886 from Senegal is presumed lost and this species is considered a nomen dubium. A key to the continental species of Afrotropical Trachelas is provided. A molecular phylogeny based on the cytochrome oxidase subunit I gene (COI) indicates that the New World species of the genus belong to a distinct lineage and are only distantly related to Trachelas sensu stricto.